The Effect of Variations in Sago Dregs Compost Dosage on the Growth and Productivity of Cucumber (Cucumis sativus L.) Plants on Marginal Land - Musdalifah, Nurul; Rupang, Maya Sari; Wa Ode Asryanti Wida Malesi; Anwar; Mani Yusuf; Johana Anike Mendes; Rizki Al Khairi Barus (Universitas Ahmad Dahlan, 2025)
This study aimed to determine the effect of applying sago waste compost on the growth and yield of cucumber (Cucumis sativus L.) cultivated in marginal land. The research was conducted using a Randomized Block Design (RBD) with one factor and five levels of compost dosage: B0 (0 tons/ha), B1 (5 tons/ha), B2 (10 tons/ha), B3 (15 tons/ha), and B4 (20 tons/ha), each replicated three times. Observed parameters included leaf number, stem diameter, plant dry weight, fruit number, fruit weight, and yield. Data were analyzed using ANOVA followed by the LSD test at a 5% significance level. The results showed that the application of sago waste compost had no significant effect on the number of leaves, stem diameter, and plant dry weight. However, the 20 tons/ha treatment (B4) significantly affected fruit weight and yield at 52 days after planting, producing the highest yield of 23.687 tons/ha. The effect was not significant at 45 and 59 days after planting. These results suggest that sago waste compost can enhance cucumber productivity during the fruit-filling phase, even though it has no significant effect on vegetative growth.).